FAKTOR – FAKTOR YANG MEMPENGARUHI PENCAPAIAN NILAI INDIKATOR KINERJA PELAKSANAAN ANGGARAN SATKER PADA KPPN MANADO - Manangin, Sri Ika Novita; Tinangon, Jantje J.; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2023)
Budget Implementation Performance Indicators (IKPA) are indicators set by the Ministry of Finance as BUN to measure the quality of budget implementation performance of State Ministries/Institutions. IKPA is used as a monitoring and evaluation tool for budget implementation, which is used as a measure and reflects the performance of work units regarding the quality of budget planning, the quality of budget implementation and the quality of budget implementation results. This research aims to find out what factors influence the achievement of IKPA values for work units at KPPN Manado. This research was conducted on 43 work units at KPPN Manado who received average and deficient predicates in the IKPA FY.2022 assessment. This research uses a questionnaire distributed to budget managers (KPA, PPK, PPSPM, Exchequer, Program and Evaluation and Procurement). Hypothesis testing uses multiple linear analysis with the help of SPSS 26. The research results show that organizational commitment, government regulations and coordination slot777 influence the achievement of the IKPA value and human resources do not influence the achievement of the IKPA value. This research is expected to increase the achievement of IKPA values for work units at KPPN Manado. Both management and employees must fulfill these four factors. Management supports employees in improving competence, motivation at work, compliance with regulations and good communication.